The repeatability of feed intake and feed efficiency in beef cattle offered high-concentrate, grass silage and pasture-based diets. (8th November 2020) - Lahart, B.; Prendiville, R.; Buckley, F.; Kennedy, E.; Conroy, S. B.; Boland, T. M.; McGee, M.
Abstract : Breeding values for feed intake and feed efficiency in beef cattle are generally derived indoors on high-concentrate (HC ) diets. Within temperate regions of north-western Europe, however, the majority of a growing beef animal's lifetime dietary intake comes from grazed grass and grass silage. Using 97 growing beef cattle, the objective of the current study was to assess the repeatability of both feed intake and feed efficiency across 3 successive dietary test periods comprising grass silage plus concentrates (S+C ), grazed grass (GRZ ) and a HC diet. Individual DM intake (DMI ), DMI/kg BW and feed efficiency-related parameters, residual feed intake (RFI ) and gain to feed ratio (G : F ) were assessed. There was a significant correlation for DMI between the S+C and GRZ periods ( r = 0.32; P < 0.01) as well as between the S+C and HC periods ( r = 0.41; P < 0.001), whereas there was no association for DMI between the GRZ and HC periods. There was a significant correlation for DMI/kg BW between the S+C and GRZ periods ( r = 0.33; P < 0.01) and between the S+C and HC periods ( r = 0.40; P < 0.001), but there was no association for the trait between the GRZ and HC periods. There was a significant correlation for RFI between the S+C and GRZ periods ( r = 0.25; P < 0.05) as well as between S+C and HC periods ( r = 0.25; P < 0.05), whereas there was no association for RFI between the GRZ and HC periods. Gain to feed ratio was not correlated between any of the test periods. A secondary aspect of the study demonstrated that traits recorded in the GRZ period relating to grazing bite rate, the number of daily grazing bouts and ruminating bouts were associated with DMI ( r = 0.28 to 0.42; P < 0.05 - 0.001), DMI/kg BW ( r = 0.36 to 0.45; P < 0.01 - 0.001) and RFI ( r = 0.31 to 0.42; P < 0.05 - 0.001). Additionally, the number of ruminating boli produced per day and per ruminating bout were associated with G : F ( r = 0.28 and 0.26, respectively; P < 0.05). Results from this study demonstrate that evaluating animals for both feed intake and feed efficiency indoors on HC diets may not reflect their phenotypic performance when consuming conserved forage-based diets indoors or when grazing pasture.